A Proposal of Quantum Theory of Life Based on Tao Science - Xiu, Rulin; Sha, Zhi Gang (Reports in Advances of Physical Sciences, 2025)
The scientific definition of life has been a subject of enduring debate, with traditional frameworks focusing on biological attributes such as cellular organization, metabolism, reproduction and adaptation. However, these approaches often fail to address the fundamental essence of life. Drawing inspiration from Erwin Schrödinger’s view of life as a process that resists entropy by sustaining order, and building on our prior work reinterpreting quantum physics through the lens of Tao science, this paper proposes a novel quantum-theoretical definition of life. We define life as a system capable of systematically maintaining, developing, enhancing, and transmitting positive information. Positive information reflects the connection, order, and harmony within a system or between the system and its environment, exemplified by phenomena such as coherence, quantum entanglement, correlation, and conditional entropy. This definition provides a foundation for exploring life’s purpose, meaning, and the root causes of challenges such as illness and dysfunction. The implications of this definition are explored in the quantitative study of life, the search for extraterrestrial life, and the development of healing and transformative techniques. By redefining life as a quantum phenomenon — consistent with the nature of all existence — this work offers insights into pathways for elevating life to its higher potential and purpose, identifies activities that may harm or diminish life, and provides a systematic framework for discovering other forms of life.